Two new species of Pleurothallis (Pleurothallidinae) subsection Macrophyllae-Fasciculatae from The Central Andes of Colombia - Sierra-Ariza, Mario Alexei (Lankesteriana: International Journal on Orchidology, 2023)
Two new species of Pleurothallis subsection Macrophyllae-Fasciculatae are described and illustrated. Both species were found in the central Andes of Colombia in the department of Tolima. The two species are compared and discussed with Pleurothallis applanata, Pleurothallis ariana-dayanae, Pleurothallis paquishae, and Pleurothallis scabrilinguis, which are the morphologically closest species. The two new species differ from their congeners mainly by lip morphology. Pleurothallis franciana is distinguished by having an oblong-lanceolate, acute, vesiculous lip with an obovate glenion, and Pleurothallis petroana is distinguished by the ovate-lanceolate, verrucose-papillose, slightly pilose lip, with a spathulate glenion.